Access to fiction for children: A user-based assessment of options and opportunities - Solomon, Paul (Information services & use, 1997)
Naturalistic observation and questioning of children grades 1-6 in school library media centers investigated their intentions, purposes, search terms, strategies, successes, and breakdowns in accessing fiction through Online Public Access Catalogs (OPACs). Presents a framework of perspectives (individual, social cultural, task, time and timing) to identify problem areas and suggests design options. (PEN)